Collective memory as a resource in Russian information warfare against Latvia - Krēķis, Jānis (Žurnalistikos tyrimai, 2015)
The paper analyses articles from the Russian language newspaper “Vesti Segodnya”, which are devoted to the war in Ukraine. The paper consists of two parts. The first part of this paper explains how the conceptualization of the information warfare has evolved during the second half of the 20th century and how the term “information warfare” is defined in Russia. Then, by looking at the theoretical foundations of collective memory, it demonstrates how collective memory has been incorporated into news stories to create resonance with current events in Ukraine. It is concluded that the usage of collective memory can be identified in articles devoted to the war in Ukraine to resonate with conflict in eastern Ukraine.
Keywords: information warfare; collective memory; Ukraine; discourse; political communication